Effect of Isotretinion on Rat’s Liver and Aptness of Cumin Oil in Protection - Prshang Tawfiq; Tuqa Yousif Sharef; Khabat Anwar Ali; Lana Sardar Salih (Diyala Journal of Medicine, 2020)
Background: Isotretinoin is a vitamin derivative also known as 13-cis-retinoic acid used in the treatment of severe acne and some forms of skin, head and neck cancer. Some studies have shown that isotretinoin induces apoptosis in various cells in the body. Isotretinion has not been clearly implicated in cases of clinically apparent acute liver injury with jaundice. The mechanism by which isotretinoin causes serum aminotransferase elevations is not known, but it may represent a direct toxic effect, in that it appears to be more frequent with higher dose therapy. For prevention or healing natural herb and its oil are used. The Cumin oil is one of these herbal oils which used as antioxidant and anti-inflammatory.